Magnitude, Extent, and Burden of Substance-use Disorders in West Bengal: Findings from the National Mental Health Survey (NMHS), 2016 - Aniruddha Basu; Pavithra Jayashankar; Aparajita Guin; Sukanto Sarkar; Pradip Kumar Saha; Raghunath Misra; Debasish Sinha; Rajarshi Neogi; Soumyadeep Saha; Vivek Benegal; Girish N Rao; Mathew Varghese; et al. (Indian Journal of Psychological Medicine)
Introduction: Substance-use disorders (SUDs) are a public health problem. The Global Adult Tobacco Survey (GATS) and National Family Health Survey (NFHS) provide evidence of high usage. Hence, the National Mental Health Survey (NMHS) WB data were analyzed to estimate the prevalence, pattern, disability burden, and service utilization of SUD. Methodology: The usual NMHS methodology was used. Four districts were selected, and thereafter, a multistage random sampling was done. The validated Bengali version of the Mini International Neuropsychiatric Interview (MINI) and other instruments like the Fagerstrom Test for Nicotine Dependence (FTND), disability, and health care utilization modules were used. Results: A total of 2,646 eligible members (age >18 years as per 2011 census) were interviewed. It was found that alcohol use as per MINI at least 3 drinks of alcohol within 3 hours on 3 or more occasions was 3.9%, and the weighted prevalence of alcohol-use disorder (AUD) and tobacco-use disorder (TUD) was 3.04% and 14%, respectively. The AUD and TUD prevalence was lower than the national prevalence, yet they were more prevalent in urban areas than in the national trend. The ratio of women to men suffering from AUD in WB (1:5) was one of the highest in the country (all India average 1:18). Also, the treatment gap of 89.2% was more than the national average. Discussion: SUDs are an important public health problem in the state of WB, which requires further research, particularly among women, comorbid psychiatric disorders, and in urban areas.